A Cross-sectional Analysis of Compassion Fatigue, Burnout, and Compassion Satisfaction in Pediatric Hematology-Oncology Physicians in the United States. Issue 1 (January 2020) - Weintraub, Andrea S.; Sarosi, Alex; Goldberg, Eliana; Waldman, Elisha D.
Abstract : Compassion fatigue (CF), burnout (BO), and compassion satisfaction (CS) are interrelated phenomena that impact personal and professional performance. The CF and Satisfaction Self-Test and a demographic questionnaire were distributed electronically to pediatric hematology-oncology physicians nationally. Linear regression models for CF, BO, and CS as a function of potential predictors were constructed. Survey response rate was 28%. Female sex, BO score, distress about a "clinical situation, " and "teaching" were associated with higher CF scores. "Administrative activities" were associated with lower CF scores. CF score, and distress about "administrative burden/academic stress" and "coworkers" were associated with higher BO scores. CS score and "socializing" were associated with lower BO scores. "Exercise, " "socializing, " and "talking with partner" were associated with higher CS scores. CF and BO scores, emotional depletion, and distress about the "work environment" and "administrative/academic burden" were associated with lower CS scores. Our data highlights the importance of strong social connections at work and at home to decrease BO and enhance CS. Professional development in leadership, communication, and conflict resolution, as well as "team building" events may perpetuate coworker relationships. Education about the importance of connectedness and self-care should begin early in medical education to cultivate robust coping mechanisms in trainees. Abstract : Supplemental Digital Content is available in the text.